Revisão e atualização sobre carcinogênese química cutânea - Guzmán-Silva, Maria Angélica (2023)
The results of experimental mouse skin tumorigenesis studies, first started in the 1940's, have Ied to many significant concepts dealing with the multistage theoty of cancer. Recent years have witnessed meaning fuI advances in the under-standing of molecular and cellular events involved in the stages of initiation, promotion and progression. This article describes the multistage skin carcinogenesis concepts and the mechanisms related to tumor initiation and promotion.